Development and Validation of Teacher Made Science Workbook of Grade 8 Students in the Philippines - Inocencio, Bernard T.; Calimlim, Adelia C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Science teaching in the 21st century society is a challenge but with the aid of effective and appropriate instructional materials, student learning is enhanced. This descriptive research sought to test and validate the teacher-made Science workbook in Grade 8. A conceptual test in Science was used to assess the level of proficiency of students and served as the basis for the development of the instructional material. Meanwhile, a researcher-made evaluation tool was used to assess the developed material’s usefulness. Results revealed that the students’ performance in Science before the use of the teacher-made workbook is Fairly Satisfactory based on the pretest mean. Meanwhile, their performance in Science after the use of the teacher-made workbook is Very Satisfactory based on the post-test mean. The study concludes that there is a significant difference in the students’ performance in Science before and after the use of the teacher-made Science workbook. Likewise, there is a low positive significant relationship between the second quarter academic grades and pretest scores and a negligible negative significant relationship between the third quarter academic grades and post-test scores. The study recommends that performance tasks, written works, and quarterly exam, may be considered as variables of academic performance in further investigation. The developed workbook can be used by Grade 8 Science teachers to enhance students’ performance in the subject and can be a good tool in developing students’ scientific literacy. The teacher-made Grade 8 Science workbook can also be used by teachers as a supplementary material in the K to 12 Curriculum.